A Not So Harmless Drudge: The Survival of Koerbagh's Bloemhof van allerley lieflijkheyd (1668). - van Heertum, Cis (Quaerendo, 2020)
This article discusses the survival of Adriaen Koerbagh's Bloemhof , a controversial work confidently claimed to be rare in bibliographies and in antiquarian booksellers' catalogues. So far, more than 70 copies have been found worldwide, in libraries and in private collections. Contemporary annotations provide additional biographical information on Koerbagh's arrest and imprisonment. The reception of Bloemhof in Dutch and—mainly—German bibliographies is also discussed in the article. An appendix with surviving copies has been added.